Creating Artist Citizens: Transformative Movements in Art Education and Programming - Pearce de Toledo, Dianne (Canadian Review of Art Education / Revue canadienne d'éducation artistique)

(untitled) (Canadian Society for Education through Art, 2024)
Increased professionalism, a powerful art market, and the technological revolution are begging for an overhaul in arts education and museum programming. This paper provides insights into alternative approaches that have emerged over the last fifty years and hints at the urgency for future iterations. During my time as an art professor, I implemented alternatives to today's art schools, such as field schools, free schools, and ek-stitutions. From fourteen years working in Mexico, I learned of social and cultural movements like rural boarding schools, the Free School of Sculpture, and the Intercultural Documentation Centre. Back in Canada, when I was working as a museum educator, my programs were influenced by concepts such as educational turns, participatory programs, museum hacking, and the social work of museums. This paper presents transformative movements in arts education and programming, each with the goal of creating artist citizens ready to participate in a global society.